Influence of extraction techniques on phenolic profiles and antioxidant activity in seeds and pulp of the African breadfruit ( Treculia africana ): insights into an underutilized resource - Alex-Benedict Atsé; Cedric Falco; Isabelle Bonnard; Anne-Cecile Ribou (Natural Product Research, 2026)

Molecular and genotoxic effects of carbamazepine and methylmercury on the gonads of Dreissena polymorpha - Clément Baratange; Tainá Rocha de Almeida; Jean Armengaud; Isabelle Bonnard; Elise David; Laurence Delahaut; Véronique Gaillet; Emmanuel Guillon; Mélodie Kielbasa; Jean-Luc Loizeau; Nicolas Maurin; Stéphanie Sayen; et al. (Aquatic Toxicology, 2025)

The metabolome of crustose coralline algae is driven by phylogeny and environmental conditions - Camille Vizon; Laura Lagourgue; Hendrikje Jorissen; Delphine Raviglione; Claude E. Payri; Isabelle Bonnard; Maggy M. Nugues (Algal Research, 2025)

Contact‐ and Water‐Mediated Interactions With an Allelopathic Macroalga Drive Distinct Coral Microbiome and Metabolome - Chloé Pozas‐Schacre; Hugo Bischoff; Camille Vizon; Delphine Raviglione; Camille Clerissi; Isabelle Bonnard; Maggy M. Nugues (Environmental Microbiology, 2025)
Macroalgal proliferation constitutes a major threat to coral reef resilience. Macroalgae can affect corals by altering their microbiome and metabolome. However, our understanding of the spatial scale of these effects and the influence of environmental factors is limited. We conducted a manipulative field experiment to investigate how interaction types (direct contact and close proximity) with the allelopathic macroalga Dictyota bartayresiana and prevailing water current influence the microbiome and metabolome of the coral Pocillopora acuta and its near‐surface seawater. Coral tissue damage was spatially constrained to the algal contact zone. Direct contact caused significant increases in harmful bacteria at the expense of beneficial ones in side coral fragments. Non‐significant changes were observed within the microbiome of apex fragments, suggesting a resistance of the coral holobiont to colony‐wide microbial colonisation. The coral metabolome responded to both algal contact and proximity. We detected several compounds potentially relevant for oxidative stress mitigation and coral defence. This metabolomic response was similar between apex and side fragments, supportive of a colony‐wide metabolomic response. In the near‐surface coral seawater, only a microbial response to algal contact was detected. We conclude that coral holobionts are capable of colony‐wide metabolomic responses to maintain homeostasis against macroalgal competitors.

Unveiling the hidden threat: Molecular, cellular and behavioral effects of dietborne inorganic mercury and methylmercury in Dreissena polymorpha - Clarisse Seguin; Alice Marant; Séverine Palacios-Paris; Isabelle Bonnard; Jean-Luc Loizeau; Elise David; Damien Rioult; Claudia Cosio (Chemosphere, 2025)

Assessment of the viral contamination of fecal origin over a wide geographical area using an active approach with Dreissena polymorpha - Marjorie Lortholarie; Julie Do Nascimento; Isabelle Bonnard; Audrey Catteau; Antoine Le Guernic; Nicolas Boudaud; Christophe Gantzer; Sabrina Guérin; Alain Geffard; Mélissa Palos-Ladeiro (Journal of Environmental Management, 2024)

Advancing environmental monitoring across the water continuum combining biomarker analysis in multiple sentinel species: A case study in the Seine-Normandie Basin (France) - Sylvain Slaby; Alain Geffard; Cédric Fisson; Matthieu Bonnevalle-Normand; Anne-Sophie Allonier-Fernandes; Rachid Amara; Anne Bado-Nilles; Isabelle Bonnard; Marc Bonnard; Mayélé Burlion-Giorgi; Amélie Cant; Audrey Catteau; et al. (Journal of Environmental Management, 2024)

Assessing viral freshwater hazard using a toxicokinetic model and Dreissena polymorpha - Julie Do Nascimento; Mélissa Palos Ladeiro; Isabelle Bonnard; Christophe Gantzer; Nicolas Boudaud; Christelle Lopes; Alain Geffard (Environmental Pollution, 2024)

Benthic cyanobacterial metabolites interact to reduce coral larval survival and settlement - Camille Vizon; Axel Urbanowiez; Delphine Raviglione; Isabelle Bonnard; Maggy M. Nugues (Harmful Algae, 2024)

Bioaccumulation and molecular effects of carbamazepine and methylmercury co-exposure in males of Dreissena polymorpha - Clément Baratange; Hugo Baali; Véronique Gaillet; Isabelle Bonnard; Laurence Delahaut; Jean-Charles Gaillard; Dominique Grandjean; Stéphanie Sayen; Andrea Gallorini; Nathalie Le Bris; David Renault; Florian Breider; et al. (Science of The Total Environment, 2023)

Integrative biomarker response - Threshold (IBR-T): Refinement of IBRv2 to consider the reference and threshold values of biomarkers - Audrey Catteau; Antoine Le Guernic; Mélissa Palos Ladeiro; Odile Dedourge-Geffard; Marc Bonnard; Isabelle Bonnard; Laurence Delahaut; Anne Bado-Nilles; Jean-Marc Porcher; Christelle Lopes; Olivier Geffard; Alain Geffard (Journal of Environmental Management, 2023)

Evaluation of the accumulation of the iodinated contrast agents diatrizoic acid and iohexol in Dreissena polymorpha mollusks - Gaëlle Daniele; Florent Lafay; Carine Arnaudguilhem; Sandra Mounicou; Alain Geffard; Isabelle Bonnard; Odile Dedourge-Geffard; Christelle Bonnefoy; Emmanuelle Vulliet (Chemosphere, 2023)

Assessment of the Chemical Diversity and Potential Toxicity of Benthic Cyanobacterial Blooms in the Lagoon of Moorea Island (French Polynesia) - Isabelle Bonnard; Louis Bornancin; Klervi Dalle; Mireille Chinain; Mayalen Zubia; Bernard Banaigs; Mélanie Roué (Journal of Marine Science and Engineering, 2020)
In the last decades, an apparent increase in the frequency of benthic cyanobacterial blooms has occurred in coral reefs and tropical lagoons, possibly in part because of global change and anthropogenic activities. In the frame of the survey of marine benthic cyanobacteria proliferating in the lagoon of Moorea Island (French Polynesia), 15 blooms were collected, mainly involving three species—Anabaena sp.1, Lyngbya majuscula and Hydrocoleum majus-B. Their chemical fingerprints, obtained through high performance liquid chromatography combined with UV detection and mass spectrometry (HPLC-UV-MS) analyses, revealed a high extent of species-specificity. The chemical profile of Anabaena sp.1 was characterized by three major cyclic lipopeptides of the laxaphycin family, whereas the one of L. majuscula was characterized by a complex mixture including tiahuramides, trungapeptins and serinol-derived malyngamides. Toxicity screening analyses conducted on these cyanobacterial samples using Artemia salina and mouse neuroblastoma cell-based (CBA-N2a) cytotoxic assays failed to show any toxicity to a degree that would merit risk assessment with regard to public health. However, the apparently increasing presence of blooms of Lyngbya, Hydrocoleum, Anabaena or other benthic cyanobacteria on coral reefs in French Polynesia encourages the implementation of ad hoc monitoring programs for the surveillance of their proliferation and potential assessment of associated hazards.

Determination of a new index of sexual maturity (ISM) in zebra mussel using flow cytometry: interest in ecotoxicology - Gabrielle Magniez; Alban Franco; Alain Geffard; Damien Rioult; Isabelle Bonnard; Laurence Delahaut; Sandrine Joachim; Gaëlle Daniele; Emmanuelle Vulliet; Jean-Marc Porcher; Marc Bonnard (Environmental Science and Pollution Research, 2018)

Determination of carbamazepine and 12 degradation products in various compartments of an outdoor aquatic mesocosm by reliable analytical methods based on liquid chromatography-tandem mass spectrometry - Gaëlle Daniele; Maëva Fieu; Sandrine Joachim; Anne Bado-Nilles; Rémy Beaudouin; Patrick Baudoin; Alice James-Casas; Sandrine Andres; Marc Bonnard; Isabelle Bonnard; Alain Geffard; Emmanuelle Vulliet (Environmental Science and Pollution Research, 2017)

Tiahuramides, novel compounds isolated from Lyngbya majuscula, display cytotoxic effects in human neuroblastoma cells - Alvariño Rebeca; Alonso Eva; Abou Mansour Eliane; Bornancin Louis; Bonnard Isabelle; Banaigs Bernard; Alfonso Amparo; Botana Luis (Frontiers in Marine Science, 2016)

Evolution, radiation and chemotaxonomy of Lamellodysidea, a demosponge genus with anti-plasmodial metabolites - Dirk Erpenbeck; John N. A. Hooper; Isabelle Bonnard; Patricia Sutcliffe; Mayuri Chandra; Pierre Perio; Carsten Wolff; Bernard Banaigs; Gert Wörheide; Cécile Debitus; Sylvain Petek (Marine Biology, 2012)

Total structure and biological properties of laxaphycins A and B, cyclic lipopeptides from the marine cyanobacteriumLyngbya majuscula - Isabelle Bonnard; Marc Rolland; Christian Francisco; Bernard Banaigs (International Journal of Peptide Research and Therapeutics, 1997)